PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII MTs POLITANI MACCIRINNAE TIKKE PADA MATERI OPERASI BENTUK ALJABAR: Applying The Cooperative Learning Model of TAI (Team Assisted Individualization) Type to Improve Students Mathematics Learning Outcomes in Class VII of MTs Politani Maccirinnae Tikke on the Algebraic Operation Material - Mirnawati Mirnawati; Mustamin Idris; Sutji Rochaminah (Universitas Tadulako, 2025)
The purpose of this study was to describe the Application of the Team Assisted Individualization (TAI) Type of Cooperative Learning Model which can improve the Mathematics Learning Outcomes of Class VII MTs Politani Maccirinnae Tikke in material on Algebraic Operations. The research subjects were 30 students of class VII, consisting of 11 male students and 19 female students, and three students were selected as informants. This research was conducted in two cycles. The results showed that the application of the TAI-type cooperative learning model could improve student learning outcomes in material for algebraic operations in class VII MTs Politani Maccirinnae Tikke by following the phases of cooperative learning, namely: at the first meeting 1) conveying goals and motivating students, the teacher conveys material and learning objectives and motivate students to be enthusiastic and actively involved in learning. Next, provide apperception by reminding the material previously studied, 2) present information, the teacher briefly describes the phases of the TAI type cooperative learning model that will be applied in learning, then the teacher distributes worksheets to be worked on individually, 3) organizes students into groups -study groups, the teacher divides students into 5 study groups (Teams), 4) guides the work and study groups, the teacher gives new LKPD to each group and conveys that individual work results are discussed in groups. The results of the discussion are concluded in the answers to the LKPD (Team Study), 5) Evaluation, the teacher appoints groups in turn to present the results of their group discussions (Whole Class Unit), 6) gives awards, the teacher announces the best group from group learning results and gives awards in the form of applause (Team Score and Team Recognition), and at the second meeting the teacher gave a final action test (Fact Test). This is indicated by the percentage of students' classical completeness in cycle I of 57.14% increasing to 80.76% in cycle II. The results of observations of teacher activity in cycle I were in the good category with a total score of 37 and an increase in cycle II was in the very good category with a total score of 45. The results of observations of student activity in cycle I were in the good category with a total score of 36 and an increase in cycle II is in the very good category with a total score of 45.